2020
DOI: 10.1021/acs.iecr.0c04637
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear System Identification for Aqueous PVA Degradation in a Continuous UV/H2O2 Tubular Photoreactor

Abstract: In this study, the performance of three black-box identification techniques using linear autoregressive with exogenous input (ARX), nonlinear ARX (NARX), and Hammerstein–Wiener (HW) algorithm to model the dynamics of UV/H2O2 continuous tubular photochemical reactor for the treatment of poly­(vinyl alcohol) (PVA) based on experimental data is investigated. In addition, the inherent nonlinearity of the reaction process is assessed. The reactor dynamics in the NARX model is estimated by wavelet, sigmoid, and tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Since the kinetics of the photochemical reactions is non-linear, the process dynamics measured by effluent pH are therefore non-linear. However, the degrees of nonlinearity is still unknown, and it was explored in a previous study (Lin et al, 2021). Thus, the process inputoutput dataset is first fitted with a linear ARX model to evaluate the possibility of low nonlinearity in the process output.…”
Section: Linear Arxmentioning
confidence: 99%
“…Since the kinetics of the photochemical reactions is non-linear, the process dynamics measured by effluent pH are therefore non-linear. However, the degrees of nonlinearity is still unknown, and it was explored in a previous study (Lin et al, 2021). Thus, the process inputoutput dataset is first fitted with a linear ARX model to evaluate the possibility of low nonlinearity in the process output.…”
Section: Linear Arxmentioning
confidence: 99%
“…The parameters of each dynamic structure, illustrated in Figure 5, are estimated based on the basic mathematical equation presented earlier. Describing each modelling structure is out of the scope of this study and has been discussed in our previous study [36,37]. Figure 6 illustrates the necessary steps prior to, during, and after the system identification.…”
Section: System Identification/modellingmentioning
confidence: 99%
“…It was observed that ARX-PID and ARX-sigmoid-PID have the best performance of all. However, the response of the NARX-sigmoid-PID was sluggish, and the ARX-PID had a considerable overshoot [36,37,75].…”
Section: Controlling Aop-based Treatment Processesmentioning
confidence: 99%
“…Though used as a leading method for degradation of organic pollutants, biological treatment can only treat wastewater that is readily degradable by living organisms. If that is not possible, researchers mainly focused on the oxidation of polyvinyl alcohol (PVA) in an Advanced Oxidation Process (AOP) such as UV/H2O2 process as an easy process owing to its relatively developed kinetics, non-selective degradation, low cost, and ease in operation at large-scale [1][2][3]. In particular, the UV/H2O2 process requires modelling to establish a control system that prevents adverse effects of PVA and residual hydrogen peroxide (H2O2) to the aquatic system and subsequent biological processes by maintaining H2O2 residuals in the treated effluent within a safe level.…”
mentioning
confidence: 99%